The new great trek: the root causes of the influx of refugees from Syria and Iraq to Europe - Kirmanj, Sherko; Oladimeji, Talibu; Abdul Ghani, Ahmad Bashawir (2016)
In 2010, a wave of political uprisings blew across the Middle East and North Africa (MENA), the result of which persists in some countries like Syria, Libya, Yemen and Egypt.That of Syria is unique given the number of people killed as well as the number of refugees that fled the country. Also, since 2003, people have been fleeing Iraq to other parts of the world.In an attempt to provide answers for such demographic mobility, this research examines those factors that impelled the Syrians and Iraqis to embark on such perilous journey to Europe in 2015, in particular.One of the factors, according to the findings of the study, is the total loss of hope for peace and change in Syria and Iraq.Thus, the article suspects that if the present political debacle in Syria and Iraq continues, the refugee will maintain their influx to Europe in 2016 and beyond.